Podcast on Listening: A Case Study on 2nd Year English Education Department Students In University - Muhammad Almer Ghazian Akbar; Tera Athena (Universitas Islam Negeri Palopo, 2025)
Listening is one of important skill in English language acquisition, serving as the parts for speaking and writing. It involves decoding and reconstructing information to understand communication fully. Traditional teaching methods often fail to engage students, making modern approaches essential. Podcasts, as digital audio or video media, have emerged as an effective tool for teaching listening comprehension. They provide accessible, engaging, and diverse content that motivates students to learn. Research indicates that podcasts positively impact students' listening skills, vocabulary, pronunciation, and accent recognition, while also enhancing their ability to interpret messages. At STKIP PGRI Bangkalan, podcasts were used to explore motivational themes, showing their potential as a versatile and engaging medium for teaching listening comprehension. This research pointing the value of podcasts in modern English language education, suggesting further exploration of their application across diverse contexts.